2019
DOI: 10.1177/1747021819879416
|View full text |Cite
|
Sign up to set email alerts
|

Is a picture really worth a thousand words? Evaluating contributions of fluency and analytic processing in metacognitive judgements for pictures in foreign language vocabulary learning

Abstract: Previous research shows that participants are overconfident in their ability to learn foreign language vocabulary from pictures compared with English translations. The current study explored whether this tendency is due to processing fluency or beliefs about learning. Using self-paced study of Swahili words paired with either picture cues or English translation cues, picture cues garnered higher confidence judgements but not faster study times, and this was true whether judgements of learning were made after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 62 publications
0
13
2
Order By: Relevance
“…Numerous studies have explored the effects of picture illustrations in improving learners’ memory retention of foreign vocabulary, which yielded inconsistent results. Some found that providing pictures alone benefited the encoding and free recall of aural foreign words (e.g., Morett, 2019); others suggested that the advantages of pictures over native translations were moderated by other factors, including learners’ sense of confidence (Carpenter & Geller, 2020), perceived ease of study (Carpenter & Olson, 2012; Lenzner et al, 2013), and timing of presentation (van den Broek et al, 2021); or some failed to find the benefits of pictures over native translations (e.g., Lotto & De Groot, 1998). For example, Morett (2019) found that for beginners, to aurally learn concrete Hungarian words, providing pictures depicting the meanings was more effective in enhancing encoding and free recall than providing native English translations and glosses.…”
Section: Effects Of Picture Illustrations On Foreign Vocabulary Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have explored the effects of picture illustrations in improving learners’ memory retention of foreign vocabulary, which yielded inconsistent results. Some found that providing pictures alone benefited the encoding and free recall of aural foreign words (e.g., Morett, 2019); others suggested that the advantages of pictures over native translations were moderated by other factors, including learners’ sense of confidence (Carpenter & Geller, 2020), perceived ease of study (Carpenter & Olson, 2012; Lenzner et al, 2013), and timing of presentation (van den Broek et al, 2021); or some failed to find the benefits of pictures over native translations (e.g., Lotto & De Groot, 1998). For example, Morett (2019) found that for beginners, to aurally learn concrete Hungarian words, providing pictures depicting the meanings was more effective in enhancing encoding and free recall than providing native English translations and glosses.…”
Section: Effects Of Picture Illustrations On Foreign Vocabulary Learningmentioning
confidence: 99%
“…Only when the sense of overconfidence was mitigated through retrieval practice or warning instructions, the participants recalled Swahili words better from pictures compared with English translations. Furthermore, beyond influencing cognitive processes, pictures have the potential to impact learners’ learning experiences (Carpenter & Geller, 2020; Lenzner et al, 2013; van den Broek et al, 2021). To offer a comprehensive understanding of the picture’s effects, this study also gathered data on learners’ experiences.…”
Section: Effects Of Picture Illustrations On Foreign Vocabulary Learningmentioning
confidence: 99%
“…When asked, many learners self-identify as “visual learners” who prefer materials with a visual component (Mayer & Massa, 2003 in Butcher, 2014) and learners predict their learning outcomes to be higher when instructional materials contain images in addition to written text, compared to text-only materials (e.g., Eitel, 2016; Jaeger & Wiley, 2014; Serra & Dunlosky, 2010). For instance, learners expect that vocabulary items that are paired with images of their meaning are learned better than the same vocabulary items paired with a written translation (Carpenter & Geller, 2020; Carpenter & Olson, 2012, Experiment 4). However, multimedia heuristics are not always accurate and might actually make learners over confident in their ability to recall learning materials that contain images (Carpenter & Geller, 2020; Carpenter & Olson, 2012).…”
Section: Potential Positive Effects Of Images: Efficient Processing O...mentioning
confidence: 99%
“…For instance, learners expect that vocabulary items that are paired with images of their meaning are learned better than the same vocabulary items paired with a written translation (Carpenter & Geller, 2020; Carpenter & Olson, 2012, Experiment 4). However, multimedia heuristics are not always accurate and might actually make learners over confident in their ability to recall learning materials that contain images (Carpenter & Geller, 2020; Carpenter & Olson, 2012). Retrieval practice with images might thus—incorrectly—appear more effective to learners than practice without images.…”
Section: Potential Positive Effects Of Images: Efficient Processing O...mentioning
confidence: 99%
“…The vocabulary mastery cannot be done spontaneously but step by step. Carpenter & Geller (2020) mentioned that there are at least three steps in processing vocabulary mastery. First is the children period, this term children can define concept vocabulary to say their concrete idea.…”
Section: Literature Reviewmentioning
confidence: 99%